2020
DOI: 10.1051/e3sconf/202020002027
|View full text |Cite
|
Sign up to set email alerts
|

Water quality analysis of the PDAM drinking water distribution network at the Baron-Ngobaran management unit, Gunungkidul Regency - Indonesia

Abstract: Baron and Ngobaran Underground Rivers are two sources of water on the southern coast of Gunungkidul Regency, Indonesia. A state-owned water utility company (PDAM) is currently distributing raw water for drinking from these underground rivers to Tanjungsari, Saptosari, Paliyan, Panggang, and Purwosari. In addition to quantity, processing raw water for this purpose needs to consider water quality. Therefore, this study was designed to assess the quality of raw water along the PDAM service lines, starting from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Gunungkidul is a karst area where surface water is typically scarce [5]. The physiography consists of Baturagung Mountains in the north, Gunungsewu Karst Area in the south, and Wonosari Basin that separates the two landscapes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Gunungkidul is a karst area where surface water is typically scarce [5]. The physiography consists of Baturagung Mountains in the north, Gunungsewu Karst Area in the south, and Wonosari Basin that separates the two landscapes [6].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli bacteria are a type of biological pollutant that can live in water bodies (Bambang et al, 2014;Reinhart & Rifani, 2021). Bacteria can thrive in stagnant water bodies or in tissues (Irshabdillah & Widyastuti, 2020;Reinhart & Rifani, 2021). Studies from Khakim & Masduqi, (2017) showed the development of E. coli bacteria in drinking water networks.…”
Section: Introductionmentioning
confidence: 99%
“…The tourism potential in the southern part of the region has made the Purwosari prepare Research area, Purwosari subdistrict, Gunungkidul Regency, Special Region of Yogyakarta [2] anything needed to attract tourists and tourism developers, such as tourism facilities development located near the tourism sites. Besides the tourism development potential, Purwosari, as a part of Gunungkidul regency that located in the Gunung Sewu karst area [3], also has a problem related to surface water sources [4]. Water source development aims to fulfill water needs for households, agriculture, industry, and tourism [5].…”
Section: Introductionmentioning
confidence: 99%
“…The tourism facilities development must be in line with the availability of water. The water pipeline network from PDAM Tirta Handayani, a local state-owned water utility company in Gunungkidul, covers only a tiny part of the Purwosari area [4]. Deep wells by a tourism developer drilled near one of the tourism sites in Purwosari produced saline water [10].…”
Section: Introductionmentioning
confidence: 99%